A non-parametric analysis of the effect of the configuration of competitive pillars on competitive efficiency. Issue 3 (25th May 2020) - Horváth, Krisztina; Lafuente, Esteban
Abstract : Purpose: This study aims to evaluate how the configuration of competitive pillars impacts businesses' competitive efficiency by using a non-parametric model, namely, data envelopment analysis (DEA), with a single constant input. Design/methodology/approach: The proposed DEA model evaluates technical inefficiency, which results from differences in the availability and allocation of resources, and configuration inefficiency, which we link to differences in the way businesses amalgamate their competitive pillars. The sample includes 115 Spanish businesses operating in manufacturing, construction, retail and knowledge-intensive business services (KIBS) sectors. Findings: The results reveal that, on an average, firms can improve their overall competitive efficiency by 53.53%. The findings suggest that the configuration of competitive pillars has important implications for efficiency analyses: human capital and strategy are the most relevant aspects shaping competitive efficiency in manufacturing and construction firms; whereas innovation emerges as the most relevant competitive aspect driving competitive efficiency in KIBS firms. Originality/value: The novelty of this study lies in the analysis of competitive efficiency in a model where efficiency can be explained by overall (industry-specific) competitive efficiency within the industry and by strategic choices on how resources and capabilities are combined within the business.